APPLICATION OF CRIMINAL SANCTIONS FOR CHILDREN AS PERPETRATORS OF MORAL CRIMES AGAINST CHILDREN - Amir Nurllah; Taufik (Adisam Publisher, 2025)
The court's verdict in the sexual intercourse against children case substituted prison time and fines with vocational education as the primary penalties. The alternative to a fine for a juvenile offender who cannot pay it is either mandatory labor training with a grace period or incarceration. Judgmental decisions involving moral crimes perpetrated against children are based on both legal and non-legal factors. The elements of the articles charged to the juvenile offender must be proven by legitimate evidence in accordance with article 184 of Law Number 8 of 1981 concerning the Criminal Procedure Code and the judge's conviction; this is one aspect of the legal considerations. The presence of a community study report prepared by the Community, the judge's observation during the hearing, and other non-juridical factors Supervisor from the Correctional Center which contains the background, family, social, economic and association of the child defendant in his environment as well as the judge's knowledge and experience in examining cases of moral crimes, especially the crime of sexual intercourse. Community advisors conduct community research only on child defendants and do not conduct community research on child victims, so that the recommendation, according to the judge, sees the best interests of the child defendant but is not necessarily the best thing for child victims. The judge in making his decision, correctly considered and based on the results of the research on the requirements but rarely accommodated the recommendations of the community's research results in his decision. This is because the Judge has an obligation to maintain a sense of justice for child victims and the benefits of sanctions for child defendants so that the verdict can be the best thing for both parties or parties related to the crime.